2022
DOI: 10.3390/antibiotics11070875
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1-Mediated In Vitro Inhibition of Plasmid Transfer Is Reversed by the Intestinal Environment

Abstract: Colistin is regarded as an antibiotic of last resort against multidrug-resistant Gram-negative bacteria, including Klebsiella pneumoniae and Escherichia coli. Colistin resistance is acquired by microorganisms via chromosome-mediated mutations or plasmid-mediated mobile colistin resistance (mcr) gene, in which the transfer of mcr is the predominant factor underlying the spread of colistin resistance. However, the factors that are responsible for the spread of the mcr gene are still unclear. In this study, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that colistin resistance hinders plasmid conjugation related to colistin resistance in vitro. However, this phenomenon was reversed in the digestive tract of mice, as bile salts and anaerobic conditions in the intestine had a positive effect on the conjugation of the mcr- 1 plasmid [ 33 ]. In addition, bile is an amphiphilic detergent molecule [ 51 ], which can cause damage to the bacterial cell membrane and increase the permeability of the bacterial cell membrane, which is conducive to conjugative transfer.…”
Section: Factors Influencing Conjugation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that colistin resistance hinders plasmid conjugation related to colistin resistance in vitro. However, this phenomenon was reversed in the digestive tract of mice, as bile salts and anaerobic conditions in the intestine had a positive effect on the conjugation of the mcr- 1 plasmid [ 33 ]. In addition, bile is an amphiphilic detergent molecule [ 51 ], which can cause damage to the bacterial cell membrane and increase the permeability of the bacterial cell membrane, which is conducive to conjugative transfer.…”
Section: Factors Influencing Conjugation In Vivomentioning
confidence: 99%
“…Hence, it is necessary to identify the factors and mechanisms affecting conjugation in vivo and develop inhibitory strategies based on these factors to prevent the spread of ARGs. In fact, there have been numerous reports about the effects of substances on in vivo conjugation [ 32 , 33 , 34 ]. Logan C Ott et al summarized the research model of conjugative transfer from computer simulation in vitro and in vivo, which reflected the real situation in the intestine and laid a foundation for further research on the factors and mechanisms affecting intestinal conjugation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%